Clinical and complication outcomes of abortions in pregnant women: insights from a tertiary care center - Mellikeri, Soumya; Deshpande, Gururaj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Abortion is a highly debated and controversial topic that has sparked intense discussions and emotions across the globe. Clinical outcomes of abortions are crucial in understanding the safety and effectiveness of different abortion methods. The present study was carried to evaluate the clinical outcomes and complications associated with the abortions in a tertiary healthcare centre. Methods: This was a prospective observational study conducted on 115 women with a gestational age <24 weeks who were admitted to the labour room for all types of abortions. The demographics and clinical manifestation of the women were recorded. Various types and methods of abortion were recorded. The post abortion complications were also recorded. Results: The most common method of abortion was missed abortion in 32.1% of the cases. The most prevalent method of abortion was the most common was by tablet mifepristone 200 mg tablet misoprostol 600 µg in 69% of the patients. Regarding post abortion complication, majority of the patients had anemia in 15 (30%) of the cases. There was a significant association between complication and abortion type (p<0.001). Conclusions: Missed abortion was the most common type and the medical method of abortion is the prevalent mode of abortion. Thus, it is important to consider the long-term effects on reproductive health that may result from complications during abortion procedures.